Education with the Paradigm of Integration-Interconnection of Science and Islam in Responding to the Challenges of Modernity at the Integral-Interconnection - Sutiono, Riki (Newinera Publisher, 2025)
Classroom-format intelligent character education (CFI-CE) combined with content mastery services (CMS) can foster the development of intelligent and honest character values in students. The purpose of this study was to examine the influence of CFI-CE and CMS on the development of intelligent and honest character values in students. Multiple linear regression analysis was used to test the proposed research hypotheses. The study population comprised all students in the Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Nias University. A purposive sampling method was used to select 45 students. The data collection tool used was a closed-ended questionnaire. The results revealed that the CFI-CE and CMS service significantly contributed to the development of intelligent and honest character values in participants, both collectively and partially. Every 1.00% increase in CFI-CE and CMS was followed by an increase in students' intelligent and honest character. Counselors are advised to plan and implement this service to foster the development of intelligent and honest character values in students.